Teoria de la eleccion racional: estructura conceptual y evolucion reciente. - Felipe Botero.; Pablo Abitbol. (Colombia Internacional, 2005)
This article hopes to facilitate dialogue within political studies by presenting a general description of the conceptual structure of Rational Choice Theory, RCT. The main goal is to present precisely and concretely the basic precepts of RCT both on its original formulation and on the adjustments that have been adopted in reply to internal and external critiques. Thus, it presents a brief discussion about how the acknowledgement of the theory’s limitations has guided some aspects of its recent evolution. The article concludes with some brief reflections on the usefulness of RCT in political science, not aimed at discussing the applicability of RCT in the social sciences, a discussion beyond the scope of the paper, but to initiate a discussion about how RCT constitutes itself as a theoretical framework that facilitates dialogue within the discipline.